TREN SOSIO-SUFISTIK DALAM TAFSIR JAWA: (Pemikiran dan Tren Tafsir Kiai Saleh Darat Semarang Dalam Kitab Faidl al-Rahman) - Abdul Wahab (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2019)
Tafsir Faidl al-Rahma>n is a work of tafsir written by one of the archipelago scholars of the namely Kiai Saleh Darat, this tafsir is written using the Java language and Arabic pegon script, the goal, in addition as a mean of communication between writers and readers who are Javanese, Java language and the writing of this pegon is also a symbol of resistance against the invaders. The method used in Tafsir Faidl-al-Rahma>n is the analytical method (tahli>li>) with the Sufistic genre or isya>ri, the Sufistic genre promoted by Kiai Saleh is very unique, because Kiai Saleh is very firm in holding principle, ie incompatibility with the Sufistic genre which is symbolic, even the genre of Sufistik that is carried by Kiai Saleh can be said as